A new approach for investigating the response of lipid membranes to electrocompression by coupling droplet mechanics and membrane biophysics. Issue 161 (11th December 2019) - El-Beyrouthy, Joyce; Makhoul-Mansour, Michelle M.; Taylor, Graham; Sarles, Stephen A.; Freeman, Eric C.
Abstract : A new method for quantifying lipid–lipid interactions within biomimetic membranes undergoing electrocompression is demonstrated by coupling droplet mechanics and membrane biophysics. The membrane properties are varied by altering the lipid packing through the introduction of cholesterol. Pendant drop tensiometry is used to measure the lipid monolayer tension at an oil–water interface. Next, two lipid-coated aqueous droplets are manipulated into contact to form a bilayer membrane at their adhered interface. The droplet geometries are captured from two angles to provide accurate measurements of both the membrane area and the contact angle between the adhered droplets. Combining the monolayer tension and contact angle measurements enables estimations of the membrane tension with respect to lipid composition. Then, the membrane is electromechanically compressed using a transmembrane voltage. Electrostatic pressure, membrane tension and the work necessary for bilayer thinning are tracked, and a model is proposed to capture the mechanics of membrane compression. The results highlight that a previously unaccounted for energetic term is produced during compression, potentially reflecting changes in the lateral membrane structure. This residual energy is eliminated in cases with cholesterol mole fractions of 0.2 and higher, suggesting that cholesterol diminishes these adjustments.